A REVIEW ON NANOSPONGES: A REVOLUTIONIZING DRUG DELIVERY SYSTEM - Harshit Srivastava, Vivek Kumar Pandey, Dr. Manju Pandey*, Mukesh Kumar Shukla, Sanjeev Kumar Dubey, Sarita Singh, Reema Yadav, Basant Lal, Rukhsar Bano (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Nano sponges are minuscule sponges that have the ability to move throughout the body and adhere to the surface, therefore facilitating the regulated and predictable release of substances. The development of a medication delivery system based on nanosponges has been a major advancement in the treatment of some biopharmaceutical problems. A polymer-based sphere called a nanosponge may be used to apply medicine topically or orally. One important step in solving these issues is the development of nanosponges. Nanosponges are microscopic sponges that resemble viruses in size and may hold a broad range of medications inside them. Many different medications may be inserted into nanosponges for targeted drug delivery. Drugs that are hydrophilic or lipophilic may be added to nanosponge. Their aqueous solubility is another noteworthy characteristic that makes it possible to utilize them more often for medication with limited solubility, improving bioavailability, lowering drug toxicity, and halting drug breakdown. This work aims to elucidate the general introduction, properties, preparation process, characterization, and uses of nanosponges.